PENINGKATAN HASIL BELAJAR TANAH DAN PUPUK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER PADA SISWA KELAS X AGRONOMI SMK NEGERI 1 MARIORIWAWO SOPPENG - Ilham Ilham; Lahming Lahming; Muhammad Rais (Jurnal Pendidikan Teknologi Pertanian, 2015)
The purpose of this research is to detects the student’s achievement in understanding soil and fertilizers subject using cooperative learning model  with Learning Together technique for X  class of the students in SMK 1 Marioriwawo Soppeng  in Agronomy major. This is a Classroom Action Research; the approach that is stimulated student’s motivation  in doing research oriented to the nature, which has 25 students as the subject of research. Cooperative learning model  with Learning Together technique can be a method that encourages students to ask actively and to convey their opinion with the strong and accurate arguments. This research applies to the cooperative learning model  with Learning Together technique. Generally, this technique is oriented on dividing tasks and student’s individual responsibility in learning as a member of the group, each member of the group gets different tasks in order to build their own understanding in the theories and facts. From the results of the research, there is a significant of student’s achievement from the first cycle to the second cycle. It shows that the implementation of cooperative learning model  with learning together technique can increase student’s achievement in understanding soil and fertilizer subject at  X  class of the students in  SMK 1 Marioriwawo Soppeng in Agronomy major